Sejarah Peradaban Islam Dalam Perkembangan Matematika - Alya Rahmadani Harahap; Dea Putri Ananda; Pinkan Indriyani Daulay; Zulham Zulham (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Mathematics is central to our daily lives and is taught from an early age. As a result, mathematics is used in various areas of life. The history of mathematics is very important to know and study because through it we can know and understand the truth and essence of math. Besides, the history of mathematics shows its connection with many other fields of science. In the history of Islamic civilization, the development of mathematics has begun since the descent of the Quran as a sacred book for the Muslims. Through the Quran, Allah comprehensively invites His creatures to study mathematical science, which can help them to do many things, especially in worship. In this journal, the author also uses methods of literature study with qualitative research to find out how the development of mathematics through Islamic civilization. Therefore, in the journal this time, the author will try to review the evolution of mathematics through the history of Islamic civilization